Coronary Angiographic Severity in Patients With Raised Plasma Homocysteine Level - Kabir, MS; Majumder, AAs; Bari, MS; Chowdhury, AW; Islam, AM (Cardiovascular Journal, 2011)
Background: Besides conventional classic risk factors of ischaemic heart disease other variables that have come under scrutiny for their potential contribution include estrogen deficiency, lipoprotein (a), plasma fibrinogen, plasminogen-activator inhibitor type I, endogenous tissue plasminogen activator (tPA), C-reactive protein and homocysteine. A number of studies have been undertaken worldwide shows strong correlation of raised fasting plasma homocysteine level with the development of atherosclerotic vascular diseases, myocardial infarction or increasing severity of coronary artery diseases. Objective: To find out the correlation of fasting plama homocysteine level with the severity of coronary artery disease in our population. Method: We undertook a study involving 100 patients of ischaemic heart disease (determined clinically & by non-invasive tests) in National Institute of Cardiovascular Diseases, Dhaka, Bangladesh, over the period of one year from January 2003 to December 2003. Out of 100 patients, 50 patients having normal homocysteine level were considered as control and another 50 patients having raised plasma homocysteine level were taken as cases. Result: Out of 50 patients, 20% had single vessel disease, 48% had double vessel disease and 32% had 3 vessel diseases. On the other hand in control group 10% patients had normal coronary artery disease, 40% had single vessel disease, 32% had double vessel disease and 18% had triple vessel disease. Conclusion: The study showed significant increase in number of coronary artery involvement by atherosclerotic lesions with increasing levels of plasma homocysteine level. Key words: Homocysteine; Coronary artery disease; Coronary angiogram. DOI: http://dx.doi.org/10.3329/cardio.v1i2.8124 Cardiovasc. j. 2009; 1(2) : 169-173